Diversity of Arbuscular mycorrhizal (AM) fungi in some common plants of marathwada region - Sarwade, P P; Chandanshive, S S; Kanade, M B; Bhale, U N (International Multidisciplinary Research Journal, 2011)
Four angiospermic plants belonging to two different families were studied for their AM association. All test plants were growing and distributed in Osmanabad district of Marathwada region in Maharashtra state. The result showed that all the four plants viz. Annona squamosa, Annona reticulata, Tinospora cordifolia and Cocculus hirsutus had AM fungal association in the roots and spore population in the rhizosphere soil. However, maximum percent root colonization of AM fungi was observed in Tinospora cordifolia (92 %) followed by others, while minimum in Annona reticulata (57.33 %). Tinospora cordifolia (320) showed more spore density whereas less in Annona squamosa (59). Total five genera of AMF was identified up to species level in which Acaulospora spp were found dominate followed by Glomus spp, Sclerocystis spp, Entrophosphora spp and Gigaspora spp were found poorely distributed.